The Integrity of Local Wisdom in Extractive Industry Regulation: A Legal Sociological Study of Environmental Resilience in Indigenous Territories - Rafifah Aqila Wafa Kaulika; Nur Laila Ramadhani; Melinda Laila Melinda (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
This study examines the integration of local wisdom into the regulatory framework of the extractive industry, focusing on strengthening environmental resilience in indigenous areas. The objective of the research is to analyze how customary norms, ecological ethics, and socio-cultural values can be integrated into the state legal system to achieve sustainable natural resource governance. The methodology employs a socio-legal approach through document analysis, in-depth interviews with customary leaders, and a review of environmental legislation. The findings indicate that communities implementing customary principles— such as the establishment of prohibited zones, communal forest management, and ecological control rituals—exhibit higher levels of environmental resilience compared to regions relying solely on formal state regulations. This study also finds an imbalance when state law marginalizes customary law, leading to increased ecological vulnerability and the weakening of environmental protection in extractive industry areas. The significance of this research lies in its contribution to the development of a hybrid governance model that strengthens co-management between the state and customary institutions. This model is expected to serve as a foundation for policy formulation, advocacy strategies, and legal reforms to promote environmental sustainability and the protection of indigenous rights. The novelty of this study lies in the development of an integrative framework that positions local wisdom as a functional legal instrument within extractive industry regulations to enhance environmental resilience.